The forest of lost souls [large type] - Koontz, Dean R. (Dean Ray), 1945- (Thorndike Press large print high octane., 2024)
Raised in the wilderness by her late great-uncle, Vida is a young woman with an almost preternatural affinity for nature, especially for the wolves that also call the forested mountains home. Formed by hard experience, by love and loss, and by the prophecies of a fortune teller, Vida just wants peace. If only nearby Kettleton County didn't cast such a dark shadow. It's where Jose Nochelobo, the love of Vida's life and a cherished local hero, died in a tragic accident. That's the official story, but Vida has reasons to doubt it. The truth can't be contained for long. Nor can the hungry men of power in Kettleton who want something too - that Vida, like Jose, should disappear forever. One by one they come for her, prepared to do anything to see their plans through to their evil end. Vida is no less prepared for them. Vida, the forest, and its formidable wonders are waiting. She will not rest until goodness and order have been restored.